The Experiences Surrounding Romantic Relationships of Korean Bisexual Individuals - Park, Jeongeun; Chung, Seojin (Frontiers in Psychology, 2023)
Introduction In recent years, the level of social and academic interest in sexual minorities has been gradually increasing. However, studies on bisexual individuals and the data on experiences of bisexual individuals outside the United States are scarce. Methods To decrease the gap in the literature, this study examined the experiences of South Korean bisexual individuals in the context of romantic relationships via semi-structured, in-depth interviews. Participants were recruited through online-based platforms, and the interview with eight participants was analyzed. Results Five main themes were identified: discovering myself as bisexual, being exposed to discrimination and exclusion, being affected by the sex of a romantic partner, protecting myself when engaging in a romantic relationship, and benefits of a romantic relationship. Discussion The findings suggest that Korea’s heteronormative system and culture were the major challenges perceived by the participants. In conclusion, this study illustrates how sociocultural norms, social acceptance, and recognition affect bisexual identity in a romantic relationship.